Alcohol promotes CPT1A-induced lipid metabolism disorder to sentinel-regulate acute pancreatitis - Zenghui Li; Xinghui Li; Hui Jiang; Jingdong Li; Bin Xiao; Yong Chen; Shunhai Jian; Mei Zeng; Xiaoming Zhang (European Journal of Medical Research)
Abstract Background and aims Previous studies have confirmed that alcohol can increase the sensitivity of the pancreas to stressors and exacerbate the severity of pancreatitis when excessive alcohol intake is combined with other causes. In the current work, this study attempted to explore how does alcohol regulate cerulein-induced acute pancreatitis, especially before inflammation occurs. Methods Proteomics was performed to analyze the differentially expressed proteins in pancreatic tissues from a rat model of pancreatitis. The metabolite levels in the pancreatic tissue, serum of rats and serum of persons with a history of alcohol consumption were detected by LC‒MS/MS. In the present study the impact of etomoxir (a carnitine palmitoyl-transferase 1A-specific inhibitor) treatment on AR42J cells treated with alcohol and the effect of etomoxir injection on the inflammatory response in an alcohol + cerulein-induced AAP rat model was evaluated. Results When treated with the same amount of cerulein, the rats that ingested alcohol presented with more severe pancreatitis. The proteomics results revealed that the fatty acid degradation pathway was closely related to the development of alcoholic acute pancreatitis, and CPT1A exhibited the greatest increase (approximately twofold increase). The products (acylcarnitines) of CPT1A were changed in the serum of persons with a history of alcohol consumption. Etomoxir treatment mitigates the influence of alcohol stimulation on the aberrant expression of proteins associated with oxidative stress, increased ROS production, mitochondrial ultrastructural alterations and mitochondrial dysfunction in AR42J cells. Etomoxir injection reduced the inflammatory response in the AAP rat model. Conclusion Alcohol upregulates CPT1A protein expression in pancreatic tissue, resulting in abnormal lipid metabolism. The products of lipid metabolism, ROS, contribute to mitochondrial ultrastructural alterations and mitochondrial dysfunction. These changes act as sentinel events that regulate acute pancreatitis.